A new substituted bis(vic-dioxime) of its mono- and dinuclear complexes - Güngör, O.; Canpolat, E.; Kaya, Mehmet (My University, 2003)
9,10-Bis(hydroxyimino)-4,8,11,15-tetra-aza-1,2,17, 18-O-di-iso-propylideneoctadecane (H2L) was synthesized by the reaction of 1,2-O-iso-propylidene-4-aza-7-aminoheptane and anti-dichloroglyoxime in ethanol, containing an excess of NaHCO3 as a buffer to neutralize the HCl formed. The mononuclear metal complexes of this ligand have been synthesized with Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) salts. H2L forms mononuclear complexes [(HL)2M] with a metal ligand ratio of 1:2 with M = Co(II)·2H2O, Ni(II) and Cu(II). Zn(II) and Cd(II) form with H2L complexes [(H2L)(Cl)2M], which have a metal-ligand ratio of 1:1 and a dinuclear complex with UO2(VI). H2L forms the dinuclear complex [(HL)2(OH)2M2] with a metal ligand ratio of 1:1 with M = UO2(VI). Structures of the ligand and its metal complexes were identified by elemental analyses, IR, 1H and 13C NMR spectra and thermogravimetric analyses (TGA).
Keywords: And uranyl(VI) complexes; Cadmium(II); Cobalt(II); Copper(II); Nickel(II); Vic-dioxime; Zinc(II)